The barley immune receptor Mla recognizes multiple pathogens and contributes to host range dynamics - Bettgenhaeuser, Jan; Hernández-Pinzón, Inmaculada; Dawson, Andrew M; Gardiner, Matthew; Green, Phon; Taylor, Jodie; Smoker, Matthew; Ferguson, John N; Emmrich, Peter; Hubbard, Amelia; Bayles, Rosemary; Waugh, Robbie; et al. (Nature communications, 2021)
Crop losses caused by plant pathogens are a primary threat to stable food production. Stripe rust (Puccinia striiformis) is a fungal pathogen of cereal crops that causes significant, persistent yield loss. Stripe rust exhibits host species specificity, with lineages that have adapted to infect wheat and barley. While wheat stripe rust and barley stripe rust are commonly restricted to their corresponding hosts, the genes underlying this host specificity remain unknown. Here, we show that three resistance genes, Rps6, Rps7, and Rps8, contribute to immunity in barley to wheat stripe rust. Rps7 cosegregates with barley powdery mildew resistance at the Mla locus. Using transgenic complementation of different Mla alleles, we confirm allele-specific recognition of wheat stripe rust by Mla. Our results show that major resistance genes contribute to the host species specificity of wheat stripe rust on barley and that a shared genetic architecture underlies resistance to the adapted pathogen barley powdery mildew and non-adapted pathogen wheat stripe rust.
Keywords: alely; šlechtění rostlin; ribozomální proteiny; Alleles; imunita rostlin; receptory imunologické; Receptors, Immunologic; nemoci rostlin; Plant Diseases; Adaptation, Physiological; Plant Proteins; Plant Immunity; zemědělské plodiny; jedlá semena; Edible Grain; Puccinia; Hordeum; Ribosomal Proteins; Crops, Agricultural; fyziologická adaptace; ječmen (rod); hostitelská specificita; rostlinné proteiny; Host Specificity; pšenice; Triticum; Plant Breeding